Pengaruh Kualitas Produk, Persepsi Harga dan Citra Merek terhadap Kepuasan Pelanggan Sale Pisang “Mawar” Jabalsari Tulungagung - Alfin Luthfiani; Muhammad Alhada Fuadilah Habib (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
MSMEs Sale Pisang "Mawar” is one of the superior potentials in Jabalsari Village which is increasingly developing amidst intense competition between MSMEs products. The marketing has also succeeded in reaching outside cities such as Kediri and Malang. This condition cannot be separated from the high customer satisfaction factor. This research aims to determine the influence of product quality, price perception and brand image on customer satisfaction at Sale Pisang "Mawar" Jabalsari Tulungagung. This research uses an associative method with a quantitative approach. The population in this study were consumers who had purchased Jabalsari Tulungagung "Mawar" Banana Sale products taken using accidental sampling technique. Samples were taken using the Lemeshow formula so that a sample size of 100 respondents was obtained. Data collection was carried out using a questionnaire. The data results were then analyzed using statistical tests with the help of the IBM SPSS 16 program. The results of this research show that product quality, price perception and brand image simultaneously have a positive and significant effect on customer satisfaction. Then, partially, product quality and perception have a positive and significant effect on customer satisfaction. However, partial brand image does not have a positive and significant effect on customer satisfaction.